"Sizing of PV storage systems for different household types". (August 2019) - Boeckl, Benjamin; Kienberger, Thomas
Highlights: Sizing PV storage systems. Differentiation of user groups. Optimizing degree of self-sufficiency. Comparison of technical optima and economic optima in sizing PV storage systems. Abstract: This paper presents a novel method of sizing PV storage systems for different household types such as single -, family –shared flats – or pensioner households. The method is based on a simulation model that characterizes the PV system including peripheral components like the inverter and the battery. The required input data to carry out the calculations is gathered from simulated household loads, characteristics of system components and measured radiation values. Sizing the grid-connected PV storage system is performed based on technical parameters only, without economic evaluation. The results show significant differences in the ideal system configuration depending on the household types ranging from a PV to battery ratio of 0.76–4.25 kWpeak /kWh. This suggests, that the household type needs to be considered before installing a PV storage system in order to ensure optimal results for the customer and the energy system. After the technical sizing, the results are compared to economic design optima, in order to investigate existing differences.